THE RELATIONSHIP OF PREGNANT WOMEN'S KNOWLEDGE WITH THE FREQUENCY OF ANTENATAL CARE VISITS IN THE INDEPENDENT PRACTICE OF MIDWIFERES L KEDUNG SALAM KARAWANG REGENCY - Soelistiawaty, Indah; Balwiah, Rida (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2025)
Background: Antenatal care services are health services provided by health workers to a pregnant woman during her pregnancy to ensure that pregnancy and childbirth do not pose a negative risk to her and her baby. Objective: To determine the relationship between knowledge of pregnant women and the frequency of antenatal care visits at PMB